Psychological Well-Being and Job Satisfaction of Kenyan Police Officers - Ndero, Peter; Kimamo, Charles; Mwaura, Lucas (International Journal of Psychology, 2024)
Purpose: Police work is a high risk job in terms of stress and low psychological wellbeing. In Kenya, police officers have presented high levels of suicide, homicide, assault and intimate partner abuse and this has become a matter of concern. Methodology: This theoretical paper applies the hermeneutic phenomenological approach to study psychological wellbeing and job satisfaction of police officers as a phenomenon and how it affects police work. Extensive and systematic literature review is done using search engines like google scholar, web of science and Scopus. The search includes historical and contemporary scholarly data which reveals how police work is understood by scholars and the media. This data is then assessed and interpreted to discern the emerging patterns, findings and conclusions. Findings: Statistics on the Kenya police service indicate that 20,000 police officers are either depressed or they present with various psychological disorders. Between 2016 and 2020 police have recorded within their ranks across the country 13 murders and 11 suicides per year without a break. Systematic literature view has revealed that high psychological wellbeing of police officers is imperative in order to remove or reduce psychological morbidity in police work. This not only decreases turnover, but also retains talent, and increases productivity. High psychological wellbeing also spills over to work teams and families in terms of happiness and wellbeing. Analysis of literature has also revealed that job satisfaction is one of the facets of psychological wellbeing at the work place. Unique Contribution to Theory, Practice and Policy: This paper proposes that police managers, and stakeholders should proactively put in place strategies that enhance job satisfaction and therefore improve the psychological wellbeing of police officers. Researchers in partnership with police management should also address the knowledge gap in explaining how police stressors finally precipitate the high rates of murders and suicide and implement solutions.